Anabolic androgenic steroids and violent offending: confounding by polysubstance abuse among 10 365 general population men. (4th November 2014) - Lundholm, Lena; Frisell, Thomas; Lichtenstein, Paul; Långström, Niklas
Abstract Background and Aims Anabolic androgenic steroid (AAS) use is associated with aggressive and violent behaviour, but it remains uncertain if this relationship is causal in humans. We examined the link between AAS use and violent crime while controlling for polysubstance abuse and additional suggested risk factors for violence. Design Cross‐sectional study of a population‐based sample. Setting In 2005, all Swedish‐born male twins aged 20–47 years were invited to participate in the Swedish Twin Adults: Genes and Environment (STAGE) survey of the Swedish Twin Register (response rate = 60%). Participants A total of 10 365 male survey participants with information on AAS use. Measurement Data on self‐reported use of AAS, alcohol and other substances, attention deficit hyperactivity disorder (ADHD) and personality disorder symptoms were linked to nation‐wide, longitudinal register information on criminal convictions, IQ, psychological functioning and childhood socio‐economic status (SES) covariates. Findings Any life‐time use of AAS was associated strongly with conviction for a violent crime [2.7 versus 0.6% in convicted and non‐convicted men, respectively; odds ratio (OR) = 5.0, 95% confidence interval (CI) = 2.7–9.3]. However, this link was substantially reduced and no longer significant when controlling for other substance abuse (OR = 1.6, 95% CI = 0.8–3.3). Controlling for IQ, psychological functioning, ADHD, personality disorder symptoms and childhood SES did not reduce the risk further. Conclusion In the general population, co‐occurring polysubstance abuse, but not IQ, other neuropsychological risks or socio‐economic status, explains most of the relatively strong association between any anabolic androgenic steroid use and conviction for a violent crime.